2021
DOI: 10.1371/journal.pbio.3001237
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-electron microscopy structures of the N501Y SARS-CoV-2 spike protein in complex with ACE2 and 2 potent neutralizing antibodies

Abstract: The recently reported “UK variant” (B.1.1.7) of SARS-CoV-2 is thought to be more infectious than previously circulating strains as a result of several changes, including the N501Y mutation. We present a 2.9-Å resolution cryo-electron microscopy (cryo-EM) structure of the complex between the ACE2 receptor and N501Y spike protein ectodomains that shows Y501 inserted into a cavity at the binding interface near Y41 of ACE2. This additional interaction provides a structural explanation for the increased ACE2 affini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
119
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(134 citation statements)
references
References 43 publications
(65 reference statements)
15
119
0
Order By: Relevance
“…For example, the RBD-targeting nAbs 2-15 and C121 exhibit a complete loss of neutralizing activity against the P.1 variant [ 121 ]. Neutralization of the B.1.1.7 variant by the RBD-targeting nAbs COVA2-15, COVA1-18, and S309 has also been found to be reduced, which might be potentially due to the N501Y mutation [ 119 ]; nevertheless, this mutation has minimal effect on the neutralizing activity of the nAbs IgG ab1 and V H -Fc ab8 [ 122 ]. In contrast to RBD-specific nAb ab6, which can neutralize a pseudotyped SARS-CoV-2 variant containing a triple mutation (K417N, E484K, N501Y), the nAbs COV2-2196, COV2-3025, COV2-2381, and S2E12 exhibit reduced neutralizing ability against the B.1.351 variant containing the E484K and N501Y mutations [ 117 , 123 ].…”
Section: Antigenic View Of the Ntd And Rbd Of Sars-cov-2 S Protein And Nab Binding Sitesmentioning
confidence: 99%
“…For example, the RBD-targeting nAbs 2-15 and C121 exhibit a complete loss of neutralizing activity against the P.1 variant [ 121 ]. Neutralization of the B.1.1.7 variant by the RBD-targeting nAbs COVA2-15, COVA1-18, and S309 has also been found to be reduced, which might be potentially due to the N501Y mutation [ 119 ]; nevertheless, this mutation has minimal effect on the neutralizing activity of the nAbs IgG ab1 and V H -Fc ab8 [ 122 ]. In contrast to RBD-specific nAb ab6, which can neutralize a pseudotyped SARS-CoV-2 variant containing a triple mutation (K417N, E484K, N501Y), the nAbs COV2-2196, COV2-3025, COV2-2381, and S2E12 exhibit reduced neutralizing ability against the B.1.351 variant containing the E484K and N501Y mutations [ 117 , 123 ].…”
Section: Antigenic View Of the Ntd And Rbd Of Sars-cov-2 S Protein And Nab Binding Sitesmentioning
confidence: 99%
“…The earliest variant to emerge and rapidly became dominant worldwide carried a D614G substitution and although studies suggested increased transmissibility ( 27 29 ), this variant was neutralized with existing monoclonal antibodies and convalescent sera ( 30 32 ). The emergence of the N501Y substitution was particularly concerning, which has been reported to be more transmissible than wild type and the D614G substitution ( 11 , 33 , 34 ). The N501Y substitution was first seen in the B.1.1.7 variant ( 23 ) and subsequently in the B.1351 ( 24 ) and P1 variants ( 35 ).…”
Section: Introductionmentioning
confidence: 99%
“…N501 interacts with several residues of hACE2 including forming a hydrogen bond with Y41 of hACE2 to stabilize the virus-binding hotspot K353 at the RBD-hACE2 interface 3 . The N501Y mutation results in insertion of the aromatic ring of Y501 into a cavity between Y41 and K353 of hACE2, which increases RBD binding affinity to hACE2 11 . This ultimately leads to greater virus transmissibility, as the B.1.1.7 lineage is reportedly 43-90% more transmissible in the UK and 40-50% more transmissible in the US than early SARS-CoV-2 strains 8,12 .…”
Section: Introductionmentioning
confidence: 99%